Scanning Electron Microscopic Observation of Platelets in Hemostasis - Shimamoto, Tatsuo; Yamazaki, Hiroh; Shimamoto, Takio (Thrombosis and Haemostasis, 1973)
To observe the very early changes in platelets during hemostasis, exposed carotid arteries of 3 rabbits were punctured with a needle, immediately fixed by 0.5% glutaraldehyde solution and their inner surface examined with a scanning electron microscope (SEM). Many platelets adhered in each case to the inner surface of the artery around the wound and all of them, whether solitary or aggregated, showed a spheroidal form with several pseudopodia.Platelets in shed blood from the incised ear vein of 3 control and 3 heparinized rabbits were fixed by glutaraldehyde and observed by SEM. The percentage of aggregated platelets was 60.9% in the control and 84.1 % in the heparinized rabbits immediately after the incision. The difference was statistically significant (P < 0.01). Sixty seconds after the incision, the percentages of aggregated platelets in the samples from the control and heparinized rabbits were 78.8% and 62.2% respectively. The difference was significant (P < 0.01). In accordance with this phenomenon, the percentage of the number of flat platelets decreased and that of altered platelets increased in the control rabbits. In the heparinized rabbits, far fewer flat platelets and larger numbers of altered platelets were observed in the samples than in those of the control rabbits immediately after the bleeding. However, 15 or 30 seconds later, the platelets of the heparinized rabbits showed fewer changes than those of the control.